ANALISIS PERBEDAAN PERTIMBANGAN HUKUM HAKIM DALAM MEMUTUS PERKARA YANG SAMA (STUDI KASUS: PUTUSAN PTUN PONTIANAK NOMOR 25/G/2020/PTUN.PTK DAN PUTUSAN PTTUN JAKARTA NOMOR 106/B/2021/PT.TUN.JKT) - Gabriella Samantha G.M.; Rasji Rasji (Jurnal Hukum Adigama, 2021)
Land registration is carried out to provide legal certainty for holders of land rights, therefore the Government requires land registration as contained in the Basic Agrarian Principles. After land registration is carried out, the holders of land rights will get a certificate as strong evidence. The certificate is issued by the National Land Agency in accordance with Government Regulation No. 24 of 1997 concerning Land Registration. In practice, there are still problems related to land certificates, which is overlapping land rights certificates. Pontianak Administrative Court (PTUN) Decision Number 25/G/2020/PTUN.PTK and the State Administrative High Court Jakarta (PTTUN) Decision Number 106/B/2021/PT.TUN.JKT are examples of cases regarding overlapping land rights certificates, causing problems that need to be studied further, namely regarding what is the basis for the legal considerations of the judges of the PTUN Pontianak and PTTUN Jakarta so that there are differences in decisions in adjudicating cases of overlapping land rights certificates in the Pontianak Administrative Court Decision Number 25/G/2020/PTUN.PTK and State Administrative High Court Jakarta Decision Number 106/B/2021 /PT.TUN.JKT. Based on the results of the research conducted, it is known that the difference in legal considerations that occurred in this case was based on the judge's error regarding the calculation of the grace period related to the administrative efforts carried out by PT Bumi Indah Raya as the Plaintiff.